Errors In Writing Descriptive Text Made By The Second Grade Students Of Smp Negeri 1 Tanon, Academic Year 2012/2013 - Prastikasari, Mega Dwi; , Prof. Dr. Endang Fauziati, M. Hum; , Dra. Dwi Haryanti, M.Hum (2013)
This study aims at describing the errors made by the second grade student of SMP Negeri 1 Tanon in their written descriptive text; identify the types of lexical errors, syntactical errors and discourse errors; describing the frequency of each type of errors; explain the dominant type of error; identify the source of error and explain the proposed remedial teaching for the students. The type of this research is descriptive qualitative research. In collecting the data, the writer uses elicitation technique and documentation. There are four steps to collect data, namely: the writer gets the data of English composition made by the students from the teacher, the writer reads every composition accurately, the writer writes again all of the erroneous sentences of the student's composition, the writer writes all the erroneous sentences into a list and used them as the data. The collected data are analyzed by using Dulay, Burt and Krashen classification of errors theory, Slamet the frequency of type of error theory and Brown source of errors theory. The results of the research show that the second grade students of SMP Negeri 1 Tanon still make 168 errors in their compositions. The writer finds that from 168 data, there are three classifications of error based on the combination of linguistic category and surface strategy taxonomy. There are lexical errors consist of 17, 26% which covers: wrong spelling 14, 88%, false friend 1, 78% and use Indonesian word/ code switching 0, 59%. Errors on syntactical errors consist of 60, 12% covering: phrase 1, 19%, the use of verb 38, 09%, pronoun 20, 81%, sentence pattern 0, 59%, determiner 0, 59%, conjunction 0, 59% and article 0, 59%. And errors on discourse consist of 20, 24% which covers of generic structure 11, 31% and component of discourse 8, 92%. It is derived from 25 types of error. The highest frequency of errors that the researcher found is the uses of verb. There are 64 or 38, 09% errors that the writer found from the total errors. The researcher also finds 2 dominant sources error, namely: interlingual transfer and intra lingual transfer.